PENGARUH MOTIVASI PEGAWAI TERHADAP PENILAIAN KINERJA DI PUSAT PENDIDIKAN DAN PELATIHAN APARATUR PERDAGANGAN, KEMENTERIAN PERDAGANGAN - Relifra; Elok Pangestika Maharani (Ekomania, 2024)
This research investigates the performance assessment and motivation level of employees at the Head Office for Education and Training for Trade Apparatus, Ministry of Trade. The research uses a qualitative approach through in-depth interviews with various employees at various levels and departments. The research results show that performance appraisal in this office is a systematic process that involves aspects such as achieving work targets, contribution to organizational goals, work behavior, and communication skills. Information technology plays an important role in automating several aspects of assessment. Employee motivation, as a key element in shaping superior performance, is influenced by supportive leadership, positive work environment, career development opportunities, work flexibility, employee involvement in decision making, and effective communication. Trade Apartment Education and Training Center, Ministry of Trade invests in employee training and development and focuses on understanding individual needs. This research provides in-depth insight into how these factors interact to create a work environment that supports, motivates and encourages superior performance.